La mariposa - Jimenez, Francisco, 1943-; Silva, Simon (Boston : Houghton Mifflin, 1998)
Because he can only speak Spanish, Francisco, son of a migrant worker, has trouble when he begins first grade, but his fascination with the caterpillar in the classroom helps him begin to fit in.
Translation of: La mariposa.
Book Links (A.L.A.), December 2001.
3-6
Accelerated Reader AR
Text in Spanish.